PENGARUH PERTUMBUHAN EKONOMI, ANGKATAN KERJA, DAN INDEKS PEMBANGUNAN MANUSIA TERHADAP PENGANGGURAN DI PROVINSI BANTEN - Kholilur Rachman Kurnianto; Wiwin Priana Primandhana (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2022)
Unemployment is a macroeconomic problem that must be addressed. Unemployment arises as a result of high labor force change rates that are not offset by the availability of diverse employment, and low labor absorption rates. This research was conducted with the aim of knowing the influence of economic growth (X1), labor force (X2), and HDI (X3) on unemployment (Y) in Banten Province for the period 2009 to 2020. Secondary data was obtained through the Central Statistics Agency (BPS) of Indonesia and Banten Province as well as the Department of Manpower and Transmigration (Disnakertrans) of Banten Province. The method used is multiple linear regression analysis with the classic assumption test is Best Linear Unbiased Estimate (BLUE) using spss program version 25. The results of the study obtained that simultaneously all free variables affect unemployment, and partially economic growth has a negative and significant effect on unemployment, partial labor force has a positive and significant effect on unemployment, and partially HDI has a negative and significant effect on unemployment in Banten Province.